2003
DOI: 10.1038/sj.gene.6363894
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced frequency of a PTPRC (CD45) exon A mutation (77C→G) in systemic sclerosis

Abstract: A point mutation in exon A (C to G transversion at position 77) of human PTPRC (CD45) has recently been associated with the development of multiple sclerosis (MS) for at least a subgroup of patients. In the present report, we studied the frequency of the 77C-->G transversion in two other autoimmune diseases namely systemic sclerosis (SSc) and systemic lupus erythematosus (SLE). The mutation was found with significantly enhanced frequency in patients suffering from SSc suggesting that PTPRC could play a role as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 14 publications
(17 reference statements)
1
34
0
Order By: Relevance
“…Therefore, the shift to smaller CD45 isoforms upon activation of T cells reduces CD45 phosphatase activity and is thought to contribute to the attenuation of T cell signaling (8,12). Such a model for the importance of CD45 alternative splicing in maintaining T cell homeostasis is supported by studies that have correlated defects in CD45 splicing regulation with susceptibility to various autoimmune diseases, including multiple sclerosis, systemic sclerosis, and autoimmune hepatitis (13)(14)(15).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, the shift to smaller CD45 isoforms upon activation of T cells reduces CD45 phosphatase activity and is thought to contribute to the attenuation of T cell signaling (8,12). Such a model for the importance of CD45 alternative splicing in maintaining T cell homeostasis is supported by studies that have correlated defects in CD45 splicing regulation with susceptibility to various autoimmune diseases, including multiple sclerosis, systemic sclerosis, and autoimmune hepatitis (13)(14)(15).…”
mentioning
confidence: 60%
“…At least two polymorphisms in CD45 exon 4 and one in CD45 exon 6 have already been described in the human population to alter CD45 isoform expression and have been potentially linked to autoimmune disease susceptibility (13)(14)(15)(22)(23)(24). These three polymorphisms all fall within or near the regulatory sequences described here or in our previous study (18).…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the disease associations of CD45 alleles described in earlier cohort studies [3], there have been several reports of C77G detected in small numbers of patients with a variety of diseases, for example, four patients with systemic lupus erythematosus (SLE) [16], one with myasthenia gravis [30], and two families with haemophagocytic lymphohistiocytosis or erythrocytic haemophagocytosis [31,32]. So far no living G77G homozygous sample has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…An increased frequency of C77G has been found in HIV [14], Langerhans cell histiocytosis [15], systemic sclerosis [16], hepatitis C [17] and autoimmune hepatitis [18], but no association with common variable immunodeficiency (CVID), Graves' disease or diabetes [10,19,20]. Furthermore, C77G individuals show lymphocyte functional abnormalities, including increased IL-2 production by memory CD4 T cells and an altered threshold for signalling through the T-cell receptor [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Because an association with MS has been confirmed in some studies (13,14) but not in others (15,16), the role of 77C3 G in MS is not yet clear. Nevertheless, recent reports on an excess of 77C3 G individuals in cohorts of patients suffering from systemic sclerosis (17), autoimmune hepatitis (18), and HIV-1 infection (19) strongly suggested that the mutation and aberrant CD45 splicing may alter the immune responses of affected individuals. With the aim of defining possible mechanisms by which 77C3 G may contribute to disease susceptibility, we searched for functional consequences of the polymorphism.…”
Section: The 77c3 G Mutation In the Human Cd45 (Ptprc) Gene Leads To mentioning
confidence: 99%